Identificación del lenguaje formal de la cultura material orfebre muisca a través de la semiótica (2022)
In this project, the importance of semiotics in the creation and production process for the industrial designer was explored and determined, through the relationship of the predominant semiotic elements (beliefs, interpretations, signs and symbolisms) and representative materials of the Muisca culture ( goldsmith crafts) according to a theoretical and historical journey.